Laboratory Experiments in Circuit Theory: Link between Theoretical Concepts and Practical Examples - Jegelevičius, D.; Pagodinas, D.; Dumbrava, V. (Elektronika ir Elektrotechnika, 2010)
The laboratory experiments in circuit theory course are dedicated for practical understanding of circuit theory concepts. In linking of Circuit theory with practice it is very important to motivate the students for learning theory and to encourage them to use this theory knowledge in practical activity. Following this situation it is a challenging task to link basic circuits and laws to the interesting practical examples that lead to be the whole physical process more comprehensible. Designing laboratory experiments of Circuit theory in the Faculty of Telecommunications and electronics, KTU simple practical examples have been complemented with some new hands-on laboratory experiments.